STUDENTS’ PERCEPTIONS ON WATCHING ENGLISH MOVIES IN RELATION TO LISTENING ACTIVITIES - Syalika, Awliya Jannati; Azhar, Fadly; Purwanti, Indah Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
bstract : The purpose of this study was to determine the English Departmentstudents’ perception on watching English movies in relation to listening activities atUniversitas Riau. This investigation used quantitative method. The data was gathered byquestionnaires. The researcher analyzed the data using SPSS. The sample for this study116 students from class A, B, and C batch 2021 who took post intermediate listening &speaking classes at English Department, Universitas Riau. The result of this study showed that English Department student at Universitas Riau have a good and positive perception on watching English movies in relation to listening activities.Key words: Perception, English Movies, Listening.